2018
DOI: 10.15641/jarer.v1i1.566
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Land Registration in Kaduna State, Nigeria

Abstract: Nigeria's land registration programmes are beset with challenges. The linkage between land, the government and the people create a complex system with unique obstacles. This research investigates the challenges of land registration in Nigeria with an in-depth study of Kaduna State. The objective is to ascertain the frequency of land registration and the factors that stand as challenges to land registration from the perspectives of households, consultants in land transactions, and the Kaduna Geographic Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…This study also showed that, title applicants lacked awareness on the value attachment to the documentation of land transaction. Furthermore, this study revealed that there was a wrong perception regarding land title registration, as some respondents believed that land title registration was needed only when they wanted to sell or take a loan from the bank [21].…”
Section: Social Factor Hindering Land Title Registration Processmentioning
confidence: 92%
“…This study also showed that, title applicants lacked awareness on the value attachment to the documentation of land transaction. Furthermore, this study revealed that there was a wrong perception regarding land title registration, as some respondents believed that land title registration was needed only when they wanted to sell or take a loan from the bank [21].…”
Section: Social Factor Hindering Land Title Registration Processmentioning
confidence: 92%
“…Nigeria's transfer fees are among the most expensive in the world, yet land is still seen as a reliable store of value and best hedge against inflation. The 1978 Act has not been reformed, and is much criticised: 'politically undemocratic, economically unproductive, but also socially segregative, particularly in its urban and non-urban dichotomy' [103][104][105][106][107].…”
Section: National Land Laws and Institutions: Colonial Legacies And New Technologiesmentioning
confidence: 99%
“…Land registration systems are introduced to facilitate the formalisation of land rights and transactions in land. A wellfunctioning and accessible land registration system provides opportunity for the protection of land rights as well as being a source of information that contributes to the reduction of transaction costs in the land market (Deininger and Feder, 2009;Nwuba and Nuhu, 2018). A formal land registration system provides information about the property rights and basic characteristics of real estate, which contributes to lowering the transaction costs associated with searches required to ascertain facts about the particulars of properties and parties to a transaction.…”
Section: Principles Of Land Registrationmentioning
confidence: 99%